(untitled) (Archive of Conferences, 2021)
Folk fairy tales tell about the past, culture, spirituality, problems and achievements of each people, the life that they lived and experienced. There are also fairy tales, in particular, the oral creativity of any person and nation, singing and singing songs, lapars, afsona and legends, which have an ancient history. From time immemorial, people inherited in the form of oral literature until the appearance of writing with the aim of bringing their dreams and life experiences from generation to generation. In the process of labor, war and battle-he created an oral literature that describes his feelings before the intensities.